GIS-Driven evaluation of suitable paddy cultivation zones/ Auni Najwa Zulnajmi ... [et al.] - Zulnajmi, Auni Najwa; Roslan, Nur Faiza Husna; Suhaimi, Nur Aliesya Athirah; Asri, Nurul Amni; Abdullah, Suzanah (2023)
Competition for agricultural land use in developed countries is increasing, leading to concerns about changes in land use patterns worldwide. In fact, the world in general has accepted this phenomenon as an inevitable trend because in any situation, area developments will continue to take place. In Malaysia, this issue is particularly relevant in Kedah, where the rice cultivation area has been decreasing over time. The decline in paddy field area could carry significant implications for the land administration system and may result in environmental problems such as drought, floods, and landslides in Alor Setar. To solve this issue, the purpose of this research is to collect data on the suitability of the establishment of new paddy fields near Alor Setar, Kedah. By examining the land use patterns and changes in the paddy area, this research will identify factors contributing to this phenomenon. Furthermore, the utilization of the Geographical Information System (GIS) will facilitate the examination of the prevailing land conditions and land utilization, thereby enabling streamlined data compilation, analysis, and visualization processes. The findings will provide valuable insights for agricultural planners, consultants, farmers, and investors seeking to establish paddy fields in Alor Setar, facilitating informed decision-making regarding land use and investment. Ultimately, this study contributes to sustainable land management practices and the preservation of agricultural and for rice production in the region.